Role of p53 and CDKN2A Inactivation in Human Squamous Cell Carcinomas. (22nd April 2007) - Pacifico, Alessia; Leone, Giovanni
Abstract : p53 tumor suppressor gene is the most commonly mutated gene in human and mouse cancers. Disruption of the p53 and Rb pathways is a fundamental trend of most human cancer cells. Inactivation of CDKN2A can lead to deregulation of these two pathways. Genetic abnormalities in CDKN2A gene have been well documented in human melanoma but their involvement in human nonmelanoma skin cancer (NMSC) and in particular in squamous cell carcinoma (SCC) is less clear. Several studies have shown that human SCCs harbour unique mutations in the p53 gene as well as inactivation of the CDKN2A gene. While mutations in the p53 gene are induced by UV radiation and represent tumor initiating events, the majority of alterations detected in the CDKN2A gene do not appear to be UV-dependent. In conclusion, in addition to p53 mutations, silencing of the CDKN2A gene might play a significant role in SCC development.